2010
DOI: 10.1542/peds.2010-1466j
|View full text |Cite
|
Sign up to set email alerts
|

Transition Planning for Youth With Sickle Cell Disease: Embedding Neuropsychological Assessment Into Comprehensive Care

Abstract: OBJECTIVE: Sickle cell disease (SCD) conveys a high risk of neuropsychological impairment due to chronic anemia, hypoxemia, cerebrovascular ischemia and stroke, in addition to causing pain and other biomedical complications. Few families accessed neuropsychological testing via the traditional referral system. In this paper, we describe a successful alternative strategy for addressing cognitive and behavioral needs of youth with SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 19 publications
(24 reference statements)
2
50
0
11
Order By: Relevance
“…Many studies have identified a need for comprehensive transition planning for SCD patients, 1,2,8,10 and some evaluate proposed models of care. 8,9,19–21 Few studies have examined facilitators and barriers in the transition process. One study identified the following threats to successful transition: beginning transition education and transition clinic after 21 years of age, having the genotype SC or Sβ+ (considered less severe forms of the disease), and not requiring chronic transfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified a need for comprehensive transition planning for SCD patients, 1,2,8,10 and some evaluate proposed models of care. 8,9,19–21 Few studies have examined facilitators and barriers in the transition process. One study identified the following threats to successful transition: beginning transition education and transition clinic after 21 years of age, having the genotype SC or Sβ+ (considered less severe forms of the disease), and not requiring chronic transfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, between 94% and 98% of children with all genotypes of SCD are now living to the age of 18 and beyond (Quinn et al, 2010). A major challenge for these emerging adults is successfully transitioning from pediatric care to adult care (Debaun & Telfair, 2012;Hankins et al, 2012b;Wills et al, 2010). The proposed study is significant because it: 1) focuses on an underserved population that is burdened by a costly health problem and 2) fills a gap in the existing literature.…”
Section: Background and Significancementioning
confidence: 99%
“…7,13,14,[16][17][18][19][20] For example, a commonly identified theme from patients is anxiety about moving from the nurturing, holistic atmosphere of pediatric care to a fragmented adult care system which may not provide access to clinicians familiar with SCD. This anxiety is exacerbated by a lack of information and guidance during the transition process, leaving several youth to believe that they were abruptly "pushed out" of their pediatric practice at a certain age rather than transitioned to an adult care provider.…”
mentioning
confidence: 99%